Analisis Pengelolaan Kasuntuk Meningkatkan Rentabilitas pada Koperasi Simpan Pinjam Purnama Kelurahan Puunaaha Kabupaten Konawe - Sri Widati; Irdawati Irdawati (Universitas Batanghari Jambi, 2022)
This study aims to identify and analyze cash management to increase profitability in the Purnama savings and loan cooperative, Puunaha Village, Konawe Regency. The analytical method used in this research is descriptive percentage by describing the Profitability of Own Capital and Economic Profitability.The results of the analysis show that in 2018, the profitability ratio of own capital was 17.96%, then in 2019 it became 20.77% and in 2020 the profitability of own capital became 24.20%. This means that it has increased by an average of 20.97% per year during 2018-2020 with an average level of development reaching 3.12%, so it can be said that the profitability ratio of own capital in the Purnama Loan and Loan cooperative is quite good in terms of these indicators. While the economic profitability ratio in 2018 was 13.98%, this number increased in 2019 by 15.68% (up 1.7%) and in 2020, it reached 18.26%. This means that it has increased by an average of 15.97% per year during 2018-2020, with an average development rate of 2.14% per year. Thus the economic profitability ratio of the Purnama savings and loan cooperatives can be said to be quite good in terms of these indicators.